Reheated humid air turbine thermo-economic analysis for power generation and marine propulsion applications. - Orts-Gonzalez, Pau Lluis (Cranfield University, 2018)
The increasing demand in the marine and energy sectors, the pursuit of more efficient designs and reducing the emissions, specially in the marine sector due to the new IMO regulation, and the deregulation of the energy sector opens a window of opportunity for the research in new advanced gas turbine based power plants for mid-scale applications. Previous studies have identified humid air turbines as promising gas turbine models, capable to compete diesel and combined cycles in terms of thermal efficiency, currently dominating the marine and energy sectors respectively. Among the different architectures, the reheated humid air turbine presents the largest potential. This thesis evaluates the thermodynamic performance and the design of a reheated humid air turbine across its design envelope. A comparison in terms of efficiency and dimensions against reference marine engines, and an economic comparison against reference power generation plants is conducted to analyse the potential of such cycle. The performance effects of the component degradation are studied to obtain the expected decay in efficiency and power. The research outcomes prove the higher thermal efficiency of the reheated humid air turbine, with a maximum value of 61.35%, compared to reference marine engines. The economic analysis for power generation applications conforms the better economic performance of the cycle compared to the combined cycle plants. In addition, the degradation of the intercooler is identified to produce several penalties in the efficiency and power output. However, these penalties could be avoided with a reduced extra investment targeted to redesign the intercooler. Overall, this research constitutes a step forward in understanding the design of the reheated humid air turbines and appreciates its potential for applications where high efficiency and density of power are of competitive advantage.
PhD in Aerospace